Human neonates prefer colostrum to mature milk: Evidence for an olfactory bias toward the "initial milk"?. Issue 5 (5th November 2020) - Klaey‐Tassone, Magali; Durand, Karine; Damon, Fabrice; Heyers, Katrin; Mezrai, Nawel; Patris, Bruno; Sagot, Paul; Soussignan, Robert; Schaal, Benoist; ,
Abstract: Objectives: Colostrum is the initial milk secretion which ingestion by neonates warrants their adaptive start in life. Colostrum is accordingly expected to be attractive to newborns. The present study aims to assess whether colostrum is olfactorily attractive for 2‐day‐old newborns when presented against mature milk or a control. Methods: The head‐orientation of waking newborns was videotaped in three experiments pairing the odors of: (a) colostrum (sampled on postpartum day 2, not from own mother) and mature milk (sampled on average on postpartum day 32, not from own mother) ( n tested newborns = 15); (b) Colostrum and control (water; n = 9); and (c) Mature milk and control ( n = 13). Results: When facing the odors of colostrum and mature milk, the infants turned their nose significantly longer toward former (32.8 vs 17.7% of a 120‐s test). When exposed to colostrum against the control, they responded in favor of colostrum (32.9 vs 16.6%). Finally, when the odor of mature milk was presented against the control, their response appeared undifferentiated (26.7 vs 28.6%). Conclusions: These results indicate that human newborns can olfactorily differentiate conspecific lacteal fluids sampled at different lactation stages. They prefer the odor of the mammary secretion ‐ colostrum ‐ collected at the lactation stage that best matches the postpartum age of their own mother. These results are discussed in the context of the earliest mother‐infant chemo‐communication. Coinciding maternal emission and offspring reception of chemosignals conveyed in colostrum may be part of the sensory precursors of attunement between mothers and infants.